2013
DOI: 10.1007/s11104-013-1663-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of potassium and sodium nutrition on leaf area components in Eucalyptus grandis trees

Abstract: Background and Aims Recent studies showed a positive tree response to Na addition in K-depleted tropical soils. Our study aimed to gain insight into the effects of K and Na fertilizations on leaf area components for a widely planted tree species. Methods Leaf expansion rates, as well as nutrient, polyol and soluble sugar concentrations, were measured from emergence to abscission of tagged leaves in 1-year-old Eucalyptus grandis plantations. Leaf cell size and water status parameters were compared 1 and 2 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 55 publications
2
44
0
4
Order By: Relevance
“…Under drought, K nutrition increases plant tolerance to water stress by making soil moisture use more efficient than in K-deficient plants and also by maintaining the pH in stroma, reducing photo-oxidative damage to chloroplasts (Cakmak and Kirby, 2008). Similarly, Battie-Laclau et al (2013) showed that K and Na ion accumulation in E. grandis leaves in response to K and Na supply, contributes to increasing leaf turgor by reducing the osmotic potential.…”
Section: Introductionmentioning
confidence: 95%
“…Under drought, K nutrition increases plant tolerance to water stress by making soil moisture use more efficient than in K-deficient plants and also by maintaining the pH in stroma, reducing photo-oxidative damage to chloroplasts (Cakmak and Kirby, 2008). Similarly, Battie-Laclau et al (2013) showed that K and Na ion accumulation in E. grandis leaves in response to K and Na supply, contributes to increasing leaf turgor by reducing the osmotic potential.…”
Section: Introductionmentioning
confidence: 95%
“…In K defi ciency treatment, leaf N and Mg concentration almost equal to that in the control, while P, Ca and S concentration increased signifi cantly (Figure 3). This inferred that function of potassium in plant would be complemented partly by other elements since potassium is of great importance as an osmolyte for adaptation (Bonilla & Bolaños 2009, Gajdanowicz et al 2010, Battie-Laclau et al 2013.…”
Section: Nutritional Status In Saplingsmentioning
confidence: 99%
“…Algunos de los elementos que han mostrado desbalances nutricionales respecto a su capacidad de suplir la demanda son el boro y el potasio. Ambos elementos Dista han evidenciado su importancia en la resistencia a la sequía (Lehto et al, 2010), y además para el caso del potasio se ha apreciado en una mayor longevidad de las hojas afectando procesos de retranslocación y uso de nutrientes (Battie-Laclau et al, 2013;Lehto et al, 2010).…”
Section: Introductionunclassified